2013
DOI: 10.1371/journal.pone.0082504
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic 1,4-Pyran Naphthoquinones Are Potent Inhibitors of Dengue Virus Replication

Abstract: Dengue virus infection is a serious public health problem in endemic areas of the world where 2.5 billion people live. Clinical manifestations of the Dengue infection range from a mild fever to fatal cases of hemorrhagic fever. Although being the most rapidly spreading mosquito-borne viral infection in the world, until now no strategies are available for effective prevention or control of Dengue infection. In this scenario, the development of compounds that specifically inhibit viral replication with minimal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Replication inhibitors targeting NS1, NS3 helicase, NS4A, NS4B, NS5 methyl transferase, and NS5 RdRp are being considered and many in vitro studies have proved their efficacy (Abdel-Magid, 2017; da Costa et al, 2013;Pelliccia et al, 2017;Yeo et al, 2015).…”
Section: Polyprotein Processing and Translation Inhibitorsmentioning
confidence: 99%
“…Replication inhibitors targeting NS1, NS3 helicase, NS4A, NS4B, NS5 methyl transferase, and NS5 RdRp are being considered and many in vitro studies have proved their efficacy (Abdel-Magid, 2017; da Costa et al, 2013;Pelliccia et al, 2017;Yeo et al, 2015).…”
Section: Polyprotein Processing and Translation Inhibitorsmentioning
confidence: 99%
“…They have shown potential as antifungal, 60 antitubercular, 61 trypanocidal, 62 and antitumor 63 agents as well as inhibitors of dengue virus replication. 64 In a previous study, we reported that naphthoquinones 1 and 2 undergo intersystem crossing to the triplet state and that they are very efficient singlet oxygen generators, with experimental quantum yields in the range 0.7-1. 65 Thus, these compounds can be considered as powerful type II photosensitizers.…”
Section: Introductionmentioning
confidence: 96%
“…23 Other possible mechanism of action include intercalation, induction of breaks in the deoxyribonucleic acid (DNA) chain and bioreductive alkylation via formation of quinone methide. 24 Among the compound inserted in the class of naphthoquinones, can be cited the droserone (6) which reduced the production of viral particle of measles virus to 50% (half maximal effective concentration, EC 50 ) at a concentration of 2 µM, 25 2-aminomethyl-3-hydroxy-1,4-naphthoquinone (7) which showed promising antiviral activity against Herpes simplex virus type-1 (HSV-1) presenting EC 50 of 0.83 µM and showed activity comparable to acyclovir, the antiviral currently used clinically, which had EC 50 of 1.09 µM, 26 the pyranaphthoquinone (8) that exhibited EC 50 of 0.3114 µM for dengue virus replication in mammalian cells 27 and the naphthoquinone trimer (9) which was inhibitor of hepatitis B virus (HBV) and had EC 50 of 0.009 µM and selective index above 3000 ( Figure 2). 28 It was shown that bis-hydroxy-1,4-naphthoquinones (10) have promising antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%